Ductility Improvement of R.C Beams with Large Web opening by using Reactive Powder Concrete Layers - Husain Khalaf Jarallah; Nidaa Qassim Jassim (Tikrit Journal of Engineering Sciences, 2018)
In this investigation the effect of large web opening on the on the behaver of beams made by normal concrete (NC) and reactive powder concrete (RPC) have been studied. The experimental work consists of casting and testing in flexure 12 rectangular simply supported reinforced concrete beams. The main parameters of this test are opening locations and normal concrete and RPC location with is the section. The ultimate loads, cracking loads, load -deflection behavior, skew of the openings (deflection at the two opposite corners of openings) and ductility were discussed. These results showed that increase ultimate loads (Pu) and stiffness by increase RPC layers. The using RPC layers increase ultimate load about (1-30) %. Using RPC in compression fiber is found to be more effective than using RPC in tension fiber. The cracking load of hybrid beam with one layer of RPC in compression fiber (having one opening) higher than NC beams by 48.5%. The ultimate strength was decreases with increases opening about (4-21)%, thus indicating that the stiffness decreases accordingly. Hybrid beams with RPC in tension fiber failed with less crack than those for hybrid beams with RPC in compression fiber at the same number of openings. The skew at opening of flexural zone show greater values than the skew at opening in shear zone for each beam until failure. The increase in the number of openings leads to increase in the ductility because it reduces the strength of beams.